Congenital obstructive posterior urethral membranes and recurrent urinary tract infection: a rare case of congenital hypertrophy of the verumontanum - Diana Bancin; Elisabeth S. Herini; Pungky Ardani Kusuma; Neti Nurani (Indonesian Pediatric Society, 2015)
Congenital obstructive posterior urethral membranes (COPUM) is a complex disease closely related to several pathological changes in kidney development and function, as a result of urinary reflux since in utero. This congenital anomaly of urinary tract potentially causes hydroureteronephrosis that is often associated with recurrent urinary tract infections and, ultimately, one of the most common causes of end-stage renal disease in children.1,2 Congenital hypertrophy of the verumontanum as part of COPUM is very rare. Only a few reports have been written on congenital hypertrophy of the vermontanum causing congenital obstructive uropathy.3-6